Project on Human Development in Chicago Neighborhoods (PHDCN): Emotionality, Activity, Sociability, and Impulsivity Temperament Survey, Wave 1, 1994-1995 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One of the measures employed by the Longitudinal Cohort Study was the Emotionality, Activity, Sociability, and Impulsivity (EASI) Temperament Survey. The EASI Temperament Survey, introduced in the mid-1970s by Arnold H. Buss and Robert Plomin, was designed to evaluate subjects based on four temperaments (emotionality, activity, sociability, and impulsivity). For the purposes of the PHDCN Longitudinal Cohort Study, the EASI Temperament Survey was administered both to subjects and primary caregivers (PC). The young adults comprising cohort 18 completed the EASI Temperament Survey as a self-report inventory, while the primary caregivers of children belonging to cohorts 3 through 15 completed the EASI Temperament measure as a parental ratings survey. Respondents were asked to determine how accurately the behaviors or personality traits mentioned, characterized the subject in question, either themselves or their child. The responses to the EASI measure were used to evaluate the subjects' various social tendencies, emotional characteristics, and personality traits.